Dual and joint estimation for speech enhancement - Gopi Tilak, V; Koteswara Rao, S (International Journal of Engineering and Technology, 2018)
Maintaining good quality and intelligibility of speech is the primary constraint in mobile communications. The present work is on the enhancement of speech under the consideration of additive white and colored noise environments using Kalman filter. Dual and Joint estimation techniques were applied and the quality of speech is analyzed through the signal to noise ratio. The techniques were applied in both ideal and practical cases for two different speech samples.
Keywords: Dual Estimation; Joint Estimation; Intelligibility; Kalman Filter; Signal To Noise Ratio